Preparedness and Readiness Strategies for Addressing the COVID-19 Pandemic in Fragile and Conflict Settings: Experiences of the Gaza Strip - Abuzerr, Samer; Abu-Aita, Said; Al-Najjar, Ismail; Abuhabib, Azzam; Al-Jourany, Heba; Zinszer, Kate (Frontiers in Public Health, 2021)
The COVID-19 pandemic is a global public health threat of serious concern, especially in conflict settings that face fragility and lack adequate resources and capacities. Gaza suffers from a blockade imposed by the Israeli occupation, environmental deterioration, confiscation of lands, demolition of houses and hospitals, restrictions on movement, lack of control over natural resources, and financial constraints. Gaza's population is consequently living in a poor humanitarian situation with high unemployment rates, poverty, over-crowdedness, and a weak health system. This makes Gaza incredibly fragile and affects its ability to respond to the COVID-19 pandemic effectively. The pandemic is expected to deepen Gaza's systems' fragility, which is already overstretched beyond their limits. This will hinder its capacity to deal with the pandemic, and other pre-existing pressing humanitarian needs. Therefore, in this review, we comprehensively explored Gaza's policy failures and successes related to the COVID-19 preparedness and response by state and non-state actors and recommend potential solutions and alternatives. We have addressed critical issues including the health system, water, sanitation, hygiene, socio-economic, education, food security, and others. In Gaza, effectiveness in combating the COVID-19 pandemic can only come from committed political will, transparency from all regulators, strategic dialogue, comprehensive planning, and active international support.